CARBON STOCK IN FOREST PLANTATIONS - A CASE STUDY IN LUOT MOUNTAIN - Quang Anh, Ha (Journal of Forestry Science and Technology, 2018)
In this paper the relationship between trunk biomass and diameter-at-breast-height (DBH), which developed by Chave et al. (2005) is applied to estimate trunk biomass then trunk carbon stock in different forest kinds. Even though this approach uses only DBH and forest density to estimate trunk biomass, the results are not significant different with in comparing with the method of using DBH and height. The average difference is 12.3%. The carbon stock in forest soil is also estimated in order to understand the two carbon sequestration pools capacity. The carbon stock in forest soil is estimated by using soil sample from three soil horizons of 0 - 10 cm; 10 - 20 cm and 20 - 30 cm. The results show that the average of trunk carbon stock is 23.04 tons/ha and varied by forest kinds. Even though using only DBH and forest density to estimate forest biomass and then carbon stock but the accuracy is acceptable. The carbon stock in forest soil increases with depth. Total amount of carbon stock in forest soil is accounted for 20.88% in comparing with total amount trunk carbon stock. The total amount of forest carbon stock in these two pools is then mapped using kringing algorithm in order to estimate for any interested location inside forest area. The estimated carbon stock in the study site is classified into three categories of low stock, moderate stock, and high stock.